Carbadox, formic acid and potato fibre as feed additives for growing pigs - Siljander-Rasi, Hilkka; Alaviuhkola, Timo; Suomi, Kaija (fi, 1998)
A growth trial was conducted on 160 pigs to evaluate the effect of different types of feed additives on performance. The barley-oats-soyabean meal-based diets were supplemented with either carbadox (0 or 50 mg/kg) or potato fibre (Povex, 0 or 20 g/kg) in the growing period, or with formic acid (0 or 8 g/kg, 85 % v/w) throughout the trial. No interactions between the feed additives were observed. Both carbadox and formic acid improved, but potato fibre tended to impair the performance of growing pigs (22-51 kg liveweight, LW). Formic acid did not affect the performance of the finishing pigs (51-102 kg LW). In the finishing period the pigs fed grower diets without carbadox or formic acid compensated fully for their reduced performance. The performance of pigs fed grower diets with potato fibre remained poorer than that of pigs fed without addition of fibre.
Keywords: Ko; lisäaineet; muurahaishappo; perunakuitu; sika; ruokinta; rehut; growth promoters